Fluctuations in Cost Management, Workforce Dynamics and Profitability in Nepal Reinsurance Company Limited - Pradhan, Sumit (Nepalese Journal of Management, 2024)
The financial trajectory of Nepal Reinsurance Company Limited in recent years demonstrates the company’s adaptation to difficulties and opportunities regarding profitability, cost management, and operational efficiency. Company saw a significant decrease in its Return on Assets (ROA) during a difficult period, presumably influenced by external factors like the pandemic; nevertheless, it has subsequently demonstrated a robust comeback. The enhancement in ROA signifies that the organization has successfully streamlined its assets and executed strategic initiatives to boost profitability. Controlling employees spending has been a crucial component of the company’s cost management approach. Following a surge in labor costs, the corporation effectively curtailed these expenditures, indicating an emphasis on optimizing workforce-related expenses, maybe via efficiency measures or modified pay frameworks. This exemplifies the firm’s dedication to maintaining financial stability by controlling staff expenditure and increasing operational efficiency. Even though the company has successfully reduced staff expenditure, the ratio of management expenses to income has increased. The potential impact of increased management expenditures on profitability, if not closely monitored, makes this growth cause for concern.